2019
DOI: 10.1172/jci124738
|View full text |Cite
|
Sign up to set email alerts
|

Targeting VLA4 integrin and CXCR2 mobilizes serially repopulating hematopoietic stem cells

Abstract: he is an Advisory Board Member for Cellworks Group, RiverVest Venture Partners, and Arch Oncology. DMM is an employee of and owns equity in Magenta Therapeutics Inc. PGR has stock in Pfizer Inc. PGR and DWG are cofounders of, consultants for, and own equity in Indalo Therapeutics, a company pursuing clinical development of RGD-binding integrin antagonists, but not of antagonists of a α4β1 (VLA4). MPR serves as a consultant for RiverVest Venture Partners, and has received research funding from Amphivena Therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 73 publications
2
39
0
Order By: Relevance
“…These observations are consistent with a report by Hoggatt and colleagues showing that treatment with a CXCR2 agonist induces bone marrow vascular permeability and HSPC mobilization (29). It is also consistent with a companion paper by Karpova and colleagues showing that CXCR2 agonist-induced HSPC mobilization is dependent, in part, on CXCR2 signaling in endothelial cells (41). However, in the Zbtb46 dtr Cxcr2 -/chimeras, CXCR2 expression is abrogated in all bone marrow stromal cells, raising the possibility that CXCR2 signaling in nonendothelial stromal cells contributes to HSPC mobilization.…”
Section: Discussionsupporting
confidence: 92%
“…These observations are consistent with a report by Hoggatt and colleagues showing that treatment with a CXCR2 agonist induces bone marrow vascular permeability and HSPC mobilization (29). It is also consistent with a companion paper by Karpova and colleagues showing that CXCR2 agonist-induced HSPC mobilization is dependent, in part, on CXCR2 signaling in endothelial cells (41). However, in the Zbtb46 dtr Cxcr2 -/chimeras, CXCR2 expression is abrogated in all bone marrow stromal cells, raising the possibility that CXCR2 signaling in nonendothelial stromal cells contributes to HSPC mobilization.…”
Section: Discussionsupporting
confidence: 92%
“…67 In this context, neutrophils have been hypothesized to boost the VLA4 agonist-induced mobilization of HSCs through the release of proteases. 67 In addition, upon stimulation with CXCR2 agonists, neutrophils could also favor the egress of HSCs from the BM niche through interplay with endothelial cells. 67 Heterogeneity and functions of peripheral blood neutrophils at the end of the G-CSF-mobilizing treatment and in the apheresis product Ex vivo studies analyzing the phenotype and functions of peripheral neutrophils following G-CSF administration for mobilization purposes are relatively rare.…”
Section: Role Of Bm Neutrophils As Mediators Of Pbsc Mobilization Durmentioning
confidence: 99%
“…67 In addition, upon stimulation with CXCR2 agonists, neutrophils could also favor the egress of HSCs from the BM niche through interplay with endothelial cells. 67 Heterogeneity and functions of peripheral blood neutrophils at the end of the G-CSF-mobilizing treatment and in the apheresis product Ex vivo studies analyzing the phenotype and functions of peripheral neutrophils following G-CSF administration for mobilization purposes are relatively rare. This is due not only to the prevalent interest of both researchers and clinicians in the yield and quality of HSCs to be transplanted but also to a long-standing view of neutrophils as short-lived cells, simply contaminants of the apheresis graft products.…”
Section: Role Of Bm Neutrophils As Mediators Of Pbsc Mobilization Durmentioning
confidence: 99%
“…Therefore, on the one hand, optimization of stem cell mobilization protocols is crucial for harvesting a high number of HSPCs for transplantation. Besides G-CSF or AMD3100, other potent co-stimulators of mobilization have been proposed for testing in the clinic including N-terminal truncated form of the human CXC chemokine GRO-beta [66], inhibitor of adhesion molecule very late antigen-4 (VLA-4) inhibitor [67] and dipeptidylpeptidase-4/CD26 (DPP4/CD26) truncation product the neurotransmitter neuropeptide Y (NPY) [68]. The armamentarium of such potential pro-mobilizing agents has increased, and recent research has also demonstrated that mobilization is enhanced by the addition of i) drugs that increase the level of S1P in PB [69], ii) inhibitors of extracellular adenosine synthesis in the bone marrow microenvironment [16, 17], or iii) inhibitors of heme oxygenase 1 (HO-1) [70, 71] and inducible nitric oxide synthetize [72], intracellular enzymes which inhibit the mobilization process.…”
Section: Strategies To Accelerate Hematopoietic Reconstitution After mentioning
confidence: 99%